Inuit Elder policy guidance for system-wide educational change in Nunavut, 2000-2013 - McGregor, Heather; McGregor, Catherine (The Canadian Association for the Study of Educational Administration, 2020)
This is an in press article that is to appear in: Canadian Journal of Educational Administration & Policy. This work is licensed under a Creative Commons Attribution 4.0 International License. Elders have been educators and experts in the Arctic for as long as people have inhabited the region. The involvement of Elders in schools and school systems has a relatively shorter history, but is more significant than has been documented to date. Elder instruction, particularly to facilitate cultural content or “culture class” began in the 1970s in some Nunavut communities. In the 1990s, teaching positions were allocated to Elders to instruct language and culture in some schools. By the year 2000, four Inuit Elder Advisors were working full-time for the Nunavut Department of Education (NDE) developing educational philosophy and other materials for schools, in collaboration with a pan-territorial Elders Advisory Committee (EAC), curriculum staff and experienced classroom teachers. Many educators and administrators in Nunavut speak about the importance of Elder involvement in schools, and yet this involvement has not been the subject of research [.]